Lung transplantation following hematopoietic stem cell transplantation: report of two cases and systematic review of literature. (21st May 2014) - Soubani, Ayman O.; Kingah, Pascal; Alshabani, Khaled; Muma, Gilbert; Haq, Athar
Abstract Background Non‐infectious pulmonary complications following hematopoietic stem cell transplantation (HSCT) are major cause of morbidity and mortality with limited treatment options. Lung transplantation (LT) has been rarely reported as a treatment option for selected HSCT recipients with these problems. Objective Describe the outcome of HSCT recipients who underwent LT. Methods Two cases of LT following HSCT from our institution are presented. Cases reported in literature were identified using English language PubMed/MEDLINE with keywords hematopoietic stem cell transplantation, bone marrow transplantation, or bronchiolitis obliterans cross‐referenced with lung transplantation. We extracted data on baseline characteristics and survival data following LT. Results Total of 84 patients are analyzed. Age at time of LT was median of 22 yr (range 1–66). Seventy‐nine patients were recipients of allogeneic HSCT. The indications for LT were bronchiolitis obliterans syndrome (BOS; 63 patients), pulmonary fibrosis (13 patients), BOS/pulmonary fibrosis (five patients), and graft‐versus‐host‐disease (GVHD) of lung (three patients). The median time between HSCT and LT was 52.3 months (range 6–240). The median follow‐up after LT was 36 months (range 0–168). During this time, BOS was documented in 25 patients. Relapse of hematological malignancy was reported in two patients, and new malignancy developed in four patients. At the end of follow‐up, 60 patients were alive and 24 patients died. The probability of survival following LT at 24 and 36 months was 0.88 (95% CI 0.78–0.93) and 0.79 (95% CI 0.67–0.87), respectively. Conclusion LT is a potential therapeutic option in selected patients with severe chronic pulmonary disease following HSCT. Further studies are needed to determine the appropriate timing and the outcome of this approach.